2020
DOI: 10.1136/bmjresp-2020-000572
|View full text |Cite|
|
Sign up to set email alerts
|

Characterisation of ICU sleep by a commercially available activity tracker and its agreement with patient-perceived sleep quality

Abstract: BackgroundA low-cost, quantitative method to evaluate sleep in the intensive care unit (ICU) that is both feasible for routine clinical practice and reliable does not yet exist. We characterised nocturnal ICU sleep using a commercially available activity tracker and evaluated agreement between tracker-derived sleep data and patient-perceived sleep quality.Patients and methodsA prospective cohort study was performed in a 40-bed ICU at a community teaching hospital. An activity tracker (Fitbit Charge 2) was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…This study is unique as it utilized a wearable device-an objective tool-to measure sleep and sleep quality, while prior studies utilized subjective methods of sleep diaries and perception of quality of sleep. 4,17,19,[30][31][32] Actigraphy was reported to be more accurate than sleep diary 4,20,21 ; similarly, reported subjective time of sleep by our residents was significantly lower than the time asleep recorded by the Fitbit. The ACGME restricted work hours for residents to improve sleep hygiene and well-being 33 ; nevertheless, this study has demonstrated that residents are sleep deprived with an average daily sleep of 5.9±1.6 hours and a deep sleep of 1.1±0.4 hours, values suboptimal to recommended total (7-9 hours) and deep sleep duration (1.5-2 hours).…”
Section: Sleep and Negative Emotionsmentioning
confidence: 44%
See 1 more Smart Citation
“…This study is unique as it utilized a wearable device-an objective tool-to measure sleep and sleep quality, while prior studies utilized subjective methods of sleep diaries and perception of quality of sleep. 4,17,19,[30][31][32] Actigraphy was reported to be more accurate than sleep diary 4,20,21 ; similarly, reported subjective time of sleep by our residents was significantly lower than the time asleep recorded by the Fitbit. The ACGME restricted work hours for residents to improve sleep hygiene and well-being 33 ; nevertheless, this study has demonstrated that residents are sleep deprived with an average daily sleep of 5.9±1.6 hours and a deep sleep of 1.1±0.4 hours, values suboptimal to recommended total (7-9 hours) and deep sleep duration (1.5-2 hours).…”
Section: Sleep and Negative Emotionsmentioning
confidence: 44%
“…Actigraphy, coupled to a wrist-wearable pedometer, is a relatively inexpensive innovative instrument that can collect objective data on sleep quality for an extended period. 20,21 Accordingly, this study aimed to measure the relationship between medical residents' emotions and both total and deep sleep as measured by a wearable device. It also sought to describe the sleep quality among residents in terms of sleep stages and explore other nonsleep predictors of the negative emotions of the residents.…”
mentioning
confidence: 99%
“…ACTG monitoring is not infallible and its limitations need to be acknowledged in terms of its potential to distinguish between voluntary and involuntary movements. Whereby, patients’ wakeful inactivity may be identified as rest or sleep, and activity associated with care interventions such as repositioning may be inaccurately identified as a wakeful state [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A full description of the sleep assessment methods has been previously published. 20 The primary outcome was to assess the difference in TST recorded by the activity tracker and patient-perceived sleep quality as evaluated by the RCSQ before and after sleep protocol implementation. The number of daily steps in the ICU (a surrogate of mobility) was also compared between groups.…”
Section: Patient Selection and Assessmentsmentioning
confidence: 99%